2016
DOI: 10.3897/bdj.4.e9042
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of British and Irish Hymenoptera - Ichneumonidae

Abstract: BackgroundThe checklist of British and Irish Ichneumonidae is revised, based in large part on the collections of the Natural History Museum, London and the National Museums of Scotland, Edinburgh. Distribution records are provided at the country level.New informationOf the 2,447 species regarded as valid and certainly identified, 214 are here recorded for the first time from the British Isles. Neorhacodinae is considered to be a separate subfamily rather than a synonym of Tersilochinae. Echthrini is treated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 84 publications
(95 reference statements)
0
11
0
Order By: Relevance
“…Cladograms showing optimization of individual characters were produced using MacClade 4.03 (Maddison and Maddison 2001) and Mesquite 2.75 (Maddison and Maddison 2011). Nodal support on parsimony cladograms is shown by optimization of morphological characters using ACCTRAN which favours reversals over parallelisms as well as by decay index values (Bremer 1994) calculated using TNT (shown as a boxed number under each node or taxon) (see Fig. 117).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Cladograms showing optimization of individual characters were produced using MacClade 4.03 (Maddison and Maddison 2001) and Mesquite 2.75 (Maddison and Maddison 2011). Nodal support on parsimony cladograms is shown by optimization of morphological characters using ACCTRAN which favours reversals over parallelisms as well as by decay index values (Bremer 1994) calculated using TNT (shown as a boxed number under each node or taxon) (see Fig. 117).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…near Shore Wood (NS427878). This species was new to the Scottish checklist of Ichneumonidae (Broad, 2016) (which included searches of the Natural History Museum collection), absent from SIRI, and confirmed as absent from the original invertebrate collections held by National Museums Scotland and World Museum Liverpool. There is a pre-existing record of I. stramentor on iRecord (https://www.brc.ac.uk/irecord/) from Handa Island, Sutherland, on 20th July 2013, but no photographs were provided and the recorder was not known to Gavin Broad, making the record unverifiable (Gavin Broad, pers.…”
mentioning
confidence: 77%
“…However, we collected only two parasitoid species, T. circumflexum and Ophioninae sp., which have very little parasitism. Broad (2016) reported that T. circumflexum parasitizes various larvae of Noctuidae. Based on the literature, there have been no reports of direct parasitism in H. armigera by T. circumflexum.…”
Section: Discussionmentioning
confidence: 99%